The COVID-19 Pandemic and the 2020 U.S. Presidential Election - Leonardo Baccini; Abel Brodeur; Stephen Weymouth (Institute of Labor Economics (IZA), 2020)
What is the effect of the COVID-19 pandemic on the 2020 U.S. presidential election? Guided by a pre-analysis plan, we estimate the effect of COVID-19 cases and deaths on the change in county-level voting for Donald Trump between 2016 and 2020. To account for potential confounders, we include a large number of COVID-19-related controls as well as demographic and socioeconomic variables. Moreover, we instrument the numbers of cases and deaths with the share of workers employed in meat-processing factories to sharpen our identification strategy. We find that COVID-19 cases negatively affected Trump's vote share. The estimated effect appears strongest in urban counties, in swing states, and in states that Trump won in 2016. A simple counterfactual analysis suggests that Trump would likely have won re-election if COVID-19 cases had been 5 percent lower. Our paper contributes to the literature of retrospective voting and demonstrates that voters hold leaders accountable for their (mis-)handling of negative shocks.
Keywords: D72; I18; 330; pre-analysis plan; COVID-19; pandemic; elections; political behavior